Etika Penggunaan Kecerdasan Buatan dalam Perspektif Teologi Moral Katolik - Roida Sihombing; Helmina Simanjuntak; Laurentius Prasetyo (STP St. Bonaventura Medan, 2026)
The development of artificial intelligence is increasingly shaping the ways human beings learn, think, and make decisions, particularly in the areas of education and moral formation. This situation raises fundamental ethical questions, especially concerning human freedom and responsibility as moral subjects. This article reflects on the use of artificial intelligence from the perspective of Catholic moral theology, taking human dignity as its primary point of departure. This study employs a qualitative approach through a method of theological reflection, drawing on Sacred Scripture, the Catholic moral tradition, official Church documents, and relevant contemporary theological literature. The findings indicate that artificial intelligence can serve as a valuable aid to human life, yet it also carries the risk of weakening human freedom and obscuring moral responsibility when used without adequate ethical reflection. Excessive reliance on AI, particularly in educational contexts, may diminish critical thinking, intellectual virtues, and the process of moral character formation. In the light of Catholic faith, artificial intelligence should be understood as an instrument at the service of the human person, rather than as a substitute for human moral agency in thinking, choosing, and acting responsibly. This reflection seeks to enrich Catholic moral theology by offering a more contextual and humane response to the ethical challenges posed by contemporary technological developments.